Development of Educational Tool Game (APE) Scooter Board Sensory for Children With Special Needs - Selvi Atesya Kesumawati; M. Haris Satria; Desi Arisandy (UNIB Press, 2022)
This study aims to develop an educational game tool (APE) that can stimulate the sensor-motor abilities of children with special needs who have problems in motor and movement development. APE was developed in addition to playing but also aims to provide education and other experiences according to their developmental age and needs. The research method used is the ADDIE development research method (Analysis, Design, Development, Implementation and Evaluation). The subjects in this study were 20 person children with mild ID and autism, aged 8-12 years consisting of 12 girls and 8 boys. This study involved 4 experts, consisting of 2 learning media experts, 1 psychologist, and 1 Adaptive Physical Educator. Based on the analysis by experts using CVI and CVR, the sensory scooter board game tool obtained a mean score of 0.6 which means it has high validity, in other words the sensory scooter board APE developed is safe, inexpensive (low cost), and stimulates the motor skills of children with special needs.